Putting the ‘extra’ back into Calvinism - Habets, Myk (Scottish journal of theology, 2009)
With a long and venerable history in both Catholic and Protestant traditions the doctrine represented by the term extra Calvinisticum has fallen out of favour within contemporary theologies of the cross. Through an examination of the history of the doctrine and its constituent features the present article advocates the reclamation of the doctrine as a necessary component for a contemporary theology of the atonement, with special emphasis on the trinitarian dimensions of the death of God on the cross. The extra Calvinisticum is then adopted to refute contemporary theologies of a suffering God.